Psychometric study of the pain drawing. Issue 4 (7th April 2017) - Trahan, Lisa H.; Cox‐Martin, Emily; Johnson, Carrie E.; Dougherty, Patrick M.; Yu, Jun; Feng, Lei; Cook, Christina; Novy, Diane M.
Abstract : The objectives of the study were to (1) assess the extent to which interrater reliability of pain drawing location and dispersion scoring methods are similar across pain disciplines in a sample of patients with cancer treatment‐induced neuropathic pain ( N = 56); and (2) investigate indicators of validity of the pain drawing in this unique sample. Patients undergoing cancer therapy completed the Brief Pain Inventory Body Map, the MD Anderson Symptom Inventory, and the McGill Pain Questionnaire. Intraclass correlation coefficients among medical and psychology professionals ranged from .93 to 99. Correlations between pain drawing score and symptom burden severity ranged from .29 to 39; correlations between pain drawing score and symptom burden interference ranged from .28 to 34. Patients who endorsed pain in the hands and feet more often described their pain as electric, numb, and shooting than patients without pain in the hands and feet. They also endorsed significantly more descriptors of neuropathic pain. Results suggest a similar understanding among members of a multidisciplinary pain team as to the location and dispersion of pain as represented by patients' pain drawings. In addition, pain drawing scores were related to symptom burden severity and interference and descriptors of neuropathic pain in expected ways.